Organizations and management in cross-cultural context - Aycan, Zeynep; Kanungo, Rabindra Nath; Mendonca, Manuel (Los Angeles : Sage, 2014)
Students with a strong grasp of the complete conceptual framework of OB theories have a greater understanding of its managerial implications, as well as their own personal and work experiences. Through this understanding, the conceptual framework is validated and OB as a subject becomes more relevant. This insightful book is designed to guide students through this crucial process. Key features: * Presents the complete conceptual framework of the relevant theories of OB giving students a clear understanding of the processes underlying human behaviour at work * Encourages students to test the relevance of these theories through reflection on their own experiences, and through participation in the experiential exercises * Provides students with the knowledge they need to develop effective strategies based on sound theory, to deal with workplaces behaviours, and become first class managers * Explores the impact of cultural and cross-cultural issues in OB and equips students with the interpersonal skills they need to manage a global workforce This book is packed with cases, exercises, discussion questions and other learning features that will prepare any OB student for the difficult but necessary task of managing behaviour in the workplace. -- Provided by publisher.
Mangaing Learning Organizations in Cross-cultural Context -- Work Motivation in Cross-cultural Context -- Behavioral Modification and Performance Management -- Communication and Conflict Management -- Leadership: Role Behaviors and Cross-cultural Perspectives -- Organizational Attitudes and Work-Life Balance -- Organizational Structure and Organizational Change -- Human Resource Management in Cross-cultural Context -- Corporate Social Responsibility and Ethics.
Includes bibliographical references and index.
Keywords: Organizational behavior -- Cross-cultural studies; Organizational behavior; Politique de l'entreprise.; Gestion du personnel; Organizational behavior; Betriebswirtschaftslehre; Management; Cross-cultural studies